PENGEMBANGAN BAHAN AJAR KOMIK IPA MATERI SISTEM PERNAFASAN MANUSIA KELAS VIII SEKOLAH MENENGAH PERTAMA (SMP) - Fenny Agustina; Destaria Sudirman; Winda Kirana Putri (Universitas Riau Kepulauan, 2014)
Innovative teaching material’s varied, interesting, contextual according to the needs of students, one of teaching material is comic. LeDoux (1994) in Porter (2010) who says comics are alternative instructional material for learning, due the involvement of emotions readers will greatly affect memory and will recall lessons learned material. This study aims to produce comic teaching materials. The teaching material are created by using Power Point 2010 and Microsoft program Adobe Photoshop. Type of research is the research and Development (R D) that uses 4D models. This comic is tested to 20 learners Grade VIII SMP Negeri 11 Batam on literary facet, cereal, graphic, communication and interest learners. In terms of literary, performance, appropriateness of content, graphics, software and communication validated by educators in SMP N 11 Batam and Universitas Riau Kepulauan lecturer 6 people. The technique of data collection is administering and exercises in which learner are then description using a Likert’s scale. Feasibility of teaching materials made from the result of the percentage of questionnaire analysis expert lecturer and aducator materials obtained by 83.9%, amounting to 81.6% of media expert, questionnaires learners by 89.05%, and from the analysis of learner training gained mastery learners by 80%. The results showed that this comic worth of teaching materials used on the human respiratory system. Keywords : Development, Comics, Human Respiratory System